Measuring bacterial oxygen consumption rate to probe metabolic signature and antimicrobial susceptibility - Chiara Scribani Rossi; Simone Angeli; Bruno Casciaro; Maria Rosa Loffredo; Maria Luisa Mangoni; Sharon Spizzichino; Giovanna Boumis; Manuel Espinosa-Urgel; Marzia Arese; Alessio Paone; Francesca Cutruzzolà; Serena Rinaldo (European Biophysics Journal, 2026)

Managing Malassezia species and related infections: new insights into recent natural and synthetic antifungal compounds and their mechanism of action - Damiano Iacovozzi; Simone Carradori; Amar Osmanović; Claudiu T. Supuran; Clemente Capasso; Andrea Angeli (Molecular Diversity, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Generative artificial intelligence and marine ecological monitoring - Luciano Ortenzi; Jacopo Aguzzi; Damianos Chatzievangelou; Eugenio Nerio Nemmi; Michele Ferrari; Ivan Masmitja; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Giacomo Picardi; Paula Espina; Simona Violino; et al. (Environmental Modelling & Software, 2026)

Sensing the Reducing Power to Determine the Cell Fate: Flavin Redox-Switches in Signal Transduction - Chiara Scribani-Rossi; Simone Angeli; Alessio Paone; Sharon Spizzichino; Federica Di Fonzo; Marzia Arese; Francesca Cutruzzolà; Alessandro Paiardini; Serena Rinaldo (Current Microbiology, 2025)
Balancing electron donors and acceptors is crucial for bacterial cell to control both anabolism and catabolism rates and to keep at minimum ROS production and the resulting oxidative stress. Efficiency of nutrients uptake and assimilation is therefore linked to the availability of electron acceptors, to finally re-cycle reduced intracellular electron shuttles belonging to catabolism via respiratory chain. In case of excess reduced electron shuttles (named high reducing power), partially reduced respiratory complexes can be populated, which in turn produce ROS and oxidative stress. This is particularly relevant in the biofilm structure, where the stratified community copes with variable environment characterized by nutrients and oxygen gradients; shortage of electron acceptors found in the deeper layers of bacterial biofilm potentially favors the intracellular increase in reducing power. To avoid this risk, bacterial biofilm promotes extracellular electron flux and re-shapes biofilm morphology to increase the surface in contact with oxygen (i.e., electron acceptors). Sensing the reducing power is therefore a strategy to re-adapt the cellular metabolism to the variation of the environmental conditions, to promote the production of defense systems scavenging ROS and finally to tune bacterial behavior, such as chemotaxis and biofilm morphology. In this review, the role of the flavins in sensing the reducing power via signal transducers is discussed, with a focus on selected examples deeply characterized so far. The possible interference of such sensing activity as a strategy to treat infections and biofilm by means of electroceutical tools, is also discussed as future perspective.

Advances in in vitro clonal propagation and tuber formation of Solanum tuberosum “Agata” through sequential hormonal treatments - Laura Fattorini; Federica Della Rovere; Rosita Silvana Fratini; Francesca Lanni; Diego Piacentini; Simone D’Angeli; Maria Maddalena Altamura; Giuseppina Falasca (Plant Biosystems, 2025)

Brassinosteroids and jasmonates mitigate arsenite- and arsenate-induced morpho-anatomical anomalies in Arabidopsis roots - Federica Della Rovere; Sara Anupama Fernando Malimage; Simone D’Angeli; Alice Peduzzi; Diego Piacentini; Maria Maddalena Altamura; Giuseppina Falasca (Plant Science, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Thermal modeling of the lunar South Pole: Application to the PROSPECT landing site - Michelangelo Formisano; Maria Cristina De Sanctis; Sarah Boazman; Alessandro Frigeri; David Heather; Gianfranco Magni; Matteo Teodori; Simone De Angelis; Marco Ferrari (Planetary and Space Science, 2024)

Clay mineralogy in west Chryse Planitia, Mars: Comparison with present and future landing sites - Jeremy Brossier; Francesca Altieri; Maria Cristina De Sanctis; Alessandro Frigeri; Marco Ferrari; Simone De Angelis; Enrico Bruschini (Planetary and Space Science, 2024)

Preliminary spectroscopic investigation of a potential Mars analog site: Lake Bagno dell’Acqua, Pantelleria, Italy - Enrico Bruschini; Marco Ferrari; Cristina Mazzoni; Stefano Fazi; Francesco Latino Chiocci; Ilaria Mazzini; Giovanna Costanzo; Simone De Angelis; Maria Cristina De Sanctis; Francesca Altieri; Jeremy Brossier; Eleonora Ammannito (Planetary and Space Science, 2024)

Synergistic synbiotic containing fructooligosaccharides and Lactobacillus delbrueckii CIDCA 133 alleviates chemotherapy-induced intestinal mucositis in mice - Laísa Macedo Tavares; Luís Cláudio Lima de Jesus; Viviane Lima Batista; Fernanda Alvarenga Lima Barroso; Andria dos Santos Freitas; Gabriela Munis Campos; Monique Ferrary Américo; Tales Fernando da Silva; Nina Dias Coelho-Rocha; Giovanna Angeli Belo; Mariana Martins Drumond; Pamela Mancha-Agresti; et al. (World Journal of Microbiology and Biotechnology, 2023)

Studying the temperature dependence of NIR reflectance spectra of selected hydrated salts dissolved in water: The case of natron, mirabilite and epsomite as representative for icy-world surfaces - Daniele Fulvio; Ciprian Popa; Vito Mennella; Federico Tosi; Simone De Angelis; Mauro Ciarniello; Alessandro Mura; Gianrico Filacchione (Icarus, 2023)

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Antibacterial and anti-biofilm activities of walnut pellicle extract ( Juglans regia L.) against coagulase-negative staphylococci - Rosaria Acquaviva; Floriana D’Angeli; Giuseppe Antonio Malfa; Simone Ronsisvalle; Adriana Garozzo; Aldo Stivala; Salvatore Ragusa; Daria Nicolosi; Mario Salmeri; Carlo Genovese (Natural Product Research, 2021)

In vitro evaluation of biological activities of Orobanche crenata Forssk. leaves extract - Carlo Genovese; Rosaria Acquaviva; Simone Ronsisvalle; Gianna Tempera; Giuseppe Antonio Malfa; Floriana D’Angeli; Salvatore Ragusa; Daria Nicolosi (Natural Product Research, 2020)

From Alpine-type sulfides to nonsulfides in the Gorno Zn project (Bergamo, Italy) - Nicola Mondillo; Federica Lupone; Maria Boni; Michael Joachimski; Giuseppina Balassone; Marcello De Angelis; Simone Zanin; Fabio Granitzio (Mineralium Deposita, 2020)

Trends in Effort and Yield of Trawl Fisheries: A Case Study From the Mediterranean Sea - Tommaso Russo; Paolo Carpentieri; Lorenzo D’Andrea; Paola De Angelis; Fabio Fiorentino; Simone Franceschini; Germana Garofalo; Lucio Labanchi; Antonio Parisi; Michele Scardi; Stefano Cataudella (Frontiers in Marine Science, 2019)

OeFAD8, OeLIP and OeOSM expression and activity in cold-acclimation of Olea europaea, a perennial dicot without winter-dormancy - Simone D’Angeli; Maya Matteucci; Laura Fattorini; Angelo Gismondi; Matteo Ludovici; Antonella Canini; Maria Maddalena Altamura (Planta, 2016)

Overexpression of AtPCS1 in tobacco increases arsenic and arsenic plus cadmium accumulation and detoxification - Letizia Zanella; Laura Fattorini; Patrizia Brunetti; Enrica Roccotiello; Laura Cornara; Simone D’Angeli; Federica Della Rovere; Maura Cardarelli; Maurizio Barbieri; Luigi Sanità di Toppi; Francesca Degola; Sylvia Lindberg; et al. (Planta, 2016)

ROS and 9-oxylipins are correlated with deoxynivalenol accumulation in the germinating caryopses of Triticum aestivum after Fusarium graminearum infection - Chiara Nobili; Simone D’Angeli; Maria Maddalena Altamura; Valeria Scala; Anna Adele Fabbri; Massimo Reverberi; Corrado Fanelli (European Journal of Plant Pathology, 2014)

Regionalization of the GOES-10 retrieval algorithm for tropical South America - Weber Andrade Gonçalves; Simone Sievert Costa; Carlos Frederico de Angelis; Jurandir Ventura Rodrigues; Rodrigo Augusto Ferreira de Souza (International Journal of Remote Sensing, 2012)

Ground-based single-frequency microwave radiometric measurement of water vapour - P. K. Karmakar; M. Maiti; Alan James P. Calheiros; Carlos Frederico Angelis; Luiz Augusto Toledo Machado; Simone Sievert Da Costa (International Journal of Remote Sensing, 2011)

Modulation of intracellular proline levels affects flowering time and inflorescence architecture in Arabidopsis - Roberto Mattioli; Daniele Marchese; Simone D’Angeli; Maria Maddalena Altamura; Paolo Costantino; Maurizio Trovato (Plant Molecular Biology, 2008)

Rooting blockage in the tobacco rac mutant occurs at the initiation phase, and induces diversion to xylem differentiation - Odile Faivre-Rampant; Jacques Dommes; Thomas Gaspar; Simone D'Angeli; Giuseppina Falasca; Maria Maddalena Altamura (Plant Biosystems, 2003)

Factors affecting in vitro shoot formation from vegetative shoot apices of apple and relationship between organogenic response and cytokinin localisation - Simone D'Angeli; Paola Lauri; Walter Dewitte; Henry Van Onckelen; Emilia Caboni (Plant Biosystems, 2001)